2022
DOI: 10.1002/mrd.23661
|View full text |Cite
|
Sign up to set email alerts
|

Managing prolific sows in tropical environments

Abstract: Litter size in modern sows has been dramatically improved in recent decades by genetic selection for highly prolific sows. In a tropical environment, the average total number of pigs born and number born alive are reported to be as high as 17.2 and 15.1 piglets per litter, respectively. Therefore, the new production target in many herds aims to achieve 30–40 pigs weaned per sow per year. Despite the improvements in litter size, the mean preweaning piglet mortality rate remains high, at between 10% and 20%, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 100 publications
(224 reference statements)
0
6
0
Order By: Relevance
“…According to Table 5, Biensen et al (1996) found that the oestradiol concentration of lactating sows in summer was lower than that of lactating sows in winter. Meanwhile, some scholars found that the concentrations of thyroid hormone, glucagon and leptin were reduced for lactating sows at 28–30°C (Renaudeau, Noblet, & Dourmad, 2003; Tummaruk et al, 2022). In the future, the heat production and food intake of lactating sows suffered from heat stress can be improved by injecting these three hormones into them.…”
Section: Resultsmentioning
confidence: 99%
“…According to Table 5, Biensen et al (1996) found that the oestradiol concentration of lactating sows in summer was lower than that of lactating sows in winter. Meanwhile, some scholars found that the concentrations of thyroid hormone, glucagon and leptin were reduced for lactating sows at 28–30°C (Renaudeau, Noblet, & Dourmad, 2003; Tummaruk et al, 2022). In the future, the heat production and food intake of lactating sows suffered from heat stress can be improved by injecting these three hormones into them.…”
Section: Resultsmentioning
confidence: 99%
“…However, this has led to an observed increase in piglet pre-weaning mortality rates, raising concerns about economic losses and animal welfare. These issues may also affect sow milk yield and piglet growth rates [ 11 , 12 ]. Thongkhuy et al [ 9 ] identified a link between the thickness of sow backfat at 109 days of gestation and their milk production from Days 3 to 10 of lactation, observing that every 1 mm increment in backfat thickness resulted in an additional 270 g of milk yield during this timeframe.…”
Section: Introductionmentioning
confidence: 99%
“…In the pig industry, litter size at birth has significantly increased over the last few decades due to intensive genetic selection. In Thailand, the total number of piglets born per litter (TB) has also increased during this period (Thongkhuy et al, 2020;Tummaruk et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the pig industry, litter size at birth has significantly increased over the last few decades due to intensive genetic selection. In Thailand, the total number of piglets born per litter (TB) has also increased during this period (Thongkhuy et al., 2020; Tummaruk et al., 2022). From 1998 to 2001, the average TB in commercial swine herds in Thailand was 9.9, ranging from 1 to 28 piglets in the major maternal line breeds, such as Landrace and Yorkshire (Tummaruk et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation